The effect of L-thyroxine replacement therapy on ischemia-modified albümin and malondialdehyde levels in patients with overt and subclinical hypothyroidism. (1st October 2016) - Erem, Cihangir; Suleyman, Akile Karacin; Civan, Nadim; Mentese, Ahmet; Nuhoglu, İrfan; Uzun, Aysegul; Coskun, Hulya; Deger, Orhan
ABSTRACT: Background and objectives : The main objective of this study was to evaluate the levels of ischemia-modified albumin (IMA) and malondialdehyde (MDA) in patients with subclinical (SHypo) and overt hypothyroidism (OHypo), and to assess the effects of levothyroxine (LT4 ) therapy on the oxidative stress (OS) parameters. We also investigated the relationships among serum thyroid hormones, lipid parameters, and IMA and MDA in these patients.Design and methods : Thirty untreated patients with OHypo, 25 untreated patients with Shypo, and 30 age- and sex-matched healthy controls were prospectively included in the study. Biochemical and hormonal parameters including IMA and MDA were evaluated in all patients just before and one month after the maintenance of euthyroidism.Results : Compared with the control subjects, the levels of MDA and triglycerides (TG) significantly increased in patients with SHypo ( p < 0.001 and p < 0.05, respectively), whereas high density lipoprotein cholesterol (HDL-C) levels significantly decreased ( p = 0.01). Patients with OHypo showed significantly high MDA, total cholesterol (TC), low density lipoprotein cholesterol (LDL-C), and TG levels ( p = 0.001, p < 0.01, p = 0.01, and p < 0.01, respectively), and significantly low HDL-C levels compared with the controls ( p < 0.05). MDA levels and lipid profile were not significantly different in the patients with OHypo when compared with the patients with SHypo. Serum IMA levels did not significantly change in patients with OHypo and SHypo compared with the controls. In the pre-treatment period, MDA levels were inversely correlated with HDL-C levels in patients with OHypo ( r : −0.471, p = 0.009). Plasma MDA and LDL-C levels significantly decreased and HDL-C levels significantly increased in the groups of OHypo and SHypo after LT4 treatment. Serum IMA levels did not significantly change with the therapy in all patient groups.Conclusions : Increased MDA levels in both patient groups represent increased lipid peroxidation which might play an important role in the pathogenesis of the atherosclerosis seen in these patients. Increased OS in patients with SHypo and OHypo could be improved by LT4 treatment. Also, MDA can be used as a reliable marker of OS and oxidative damage, while IMA is considered to be inappropriate.